Upaya Peningkatan Ekonomi Warga Pantai Tirang Melalui Paiwisata Pantai - Sulistyowati, Sulistyowati; Mulatsih, Retno; Sri Sumantri, Andar; Tuzaka, Eliya (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
The community service program to improve the tourism economy at Tirang Beach, Semarang aims to increase community income through developing tourism potential on the beach. This program will be implemented through tourism product development activities, improving the quality of tourism services, and skills training for the surrounding community. The method to be used in this program is data collection through a survey to find out the tourism potential in Tirang Beach, and the needs and expectations of tourists. Furthermore, tourism products will be developed in accordance with existing potential, such as developing culinary specialties from the beach, developing handicrafts, and developing natural tourism activities such as snorkeling and diving. In addition, there will be improvements to the quality of tourism services, such as developing tourism infrastructure, making information boards, and training the local community in good and friendly tourism services to tourists. In addition, skills training will be conducted for the surrounding community to improve the quality of tourism products and services provided. The expected results of this program are increasing people's income through developing tourism potential in Tirang Beach, as well as improving the quality of tourism products and services provided. This program is also expected to attract tourists to visit Tirang Beach, so as to increase tourism potential in the area. With this program, it is hoped that the surrounding community will become more independent and be able to improve the economy through existing tourism potential. Thus, a healthier and more sustainable environment can be created through sustainable economic development.